2016
DOI: 10.1016/j.jadohealth.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Breast on Sport and Exercise Participation in School Girls in the United Kingdom

Abstract: As most of the breast concerns raised in this survey could be addressed via education and 87% of girls wanted to know more about breasts, this study demonstrates a need for breast education for school girls, which may reduce the influence of the breast on sport and exercise participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 24 publications
(21 reference statements)
3
36
1
7
Order By: Relevance
“…Previous research has demonstrated that larger breasted women perceive themselves at greater risk of developing breast cancer (Asobayire and Barley, 2014). Furthermore, larger breasted females reportedly experience higher incidence of breast issues such as breast pain and incorrect bra fit, compared to smaller breasted females (Brown et al, 2014a,b;Scurr et al, 2011Scurr et al, , 2016. However, in this study breast size showed no association with schoolgirls desire to know more about breast cancer.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Previous research has demonstrated that larger breasted women perceive themselves at greater risk of developing breast cancer (Asobayire and Barley, 2014). Furthermore, larger breasted females reportedly experience higher incidence of breast issues such as breast pain and incorrect bra fit, compared to smaller breasted females (Brown et al, 2014a,b;Scurr et al, 2011Scurr et al, , 2016. However, in this study breast size showed no association with schoolgirls desire to know more about breast cancer.…”
contrasting
confidence: 56%
“…Electronic submissions were automatically logged. A more detailed description of survey methods is presented elsewhere (Scurr et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…To explore the need for breast education, sections two and three investigated schoolgirls feelings about their breasts and breast concerns. Section four explored preferences for breast education content and section five focused on sport participation related breast concerns (published elsewhere . Finally, section six explored delivery and timing preferences for breast education.…”
Section: Methodsmentioning
confidence: 99%
“…Section four explored preferences for breast education content and section five focused on sport participation related breast concerns (published elsewhere. 16 Finally, section six explored delivery and timing preferences for breast education.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from being a potential marker of health and fertility from an anthropological point of view, breast size has been shown to affect women’s quality of life and well-being in many ways – socially, psychologically and physically 3 . For example, several studies on sport and exercise participation in adolescent girls revealed large breasts to be a cause of physical strain and a major reason why they do not take part in physical activity 4 , 5 . Back problems are also more common among women who are more well-endowed 6 .…”
Section: Introductionmentioning
confidence: 99%